Collaborative collection development: current perspectives leading to future initiatives - Levenson, Helen N. (Journal of Academic Librarianship, 2020)
As academic libraries continue to face acquisition budget challenges, collaborative collection development (CCD) offers greater opportunities to fulfill the core role of library collecting and collection management, namely, to provide enhanced access to the widest variety of relevant resources in the most cost-responsible manner possible. Libraries have successfully implemented CCD projects of various types, and as a result, have achieved these needed cost savings. The authors conducted survey research to investigate current CCD activities and librarians' perceptions of its benefits, drawbacks, elements contributing to successful CCD programs, and possible obstacles to success. Library collections consist of a variety of material formats and librarians have applied CCD models to maintain needed access to these resources, shifting from ownership to access, all in support of building collective collections. The survey results found that, although challenges can exist, application of CCD activities have realized substantial benefits, financial and otherwise, for academic libraries overall.